Elevated Systemic Pentraxin-3 Is Associated With Complement Consumption in the Acute Phase of Thrombotic Microangiopathies - Trojnar, Eszter; Józsi, Mihály; Szabó, Zsóka; Réti, Marienn; Farkas, Péter; Kelen, Kata; Reusz, George S.; Szabó, Attila J.; Garam, Nóra; Mikes, Bálint; Sinkovits, György; Mező, Blanka; et al. (Frontiers in Immunology, 2019)
Pentraxin-3 (PTX3) and C-reactive protein (CRP) have been shown to regulate complement activation in vitro, but their role has not been investigated in complement consumption in vivo. Thrombotic microangiopathies (TMA) are often accompanied by complement overactivation and consumption, therefore we analyzed the relation of the systemic pentraxin levels to the complement profile, laboratory parameters and clinical outcome of TMA patients. We determined the PTX3 and CRP levels, complement factor and activation product concentrations in blood samples of 171 subjects with the diagnosis of typical hemolytic uremic syndrome (STEC-HUS) (N=34), atypical HUS (aHUS) (N=44), secondary TMA (N=63), thrombotic thrombocytopenic purpura (TTP) (N=30) and 69 age-matched healthy individuals. Clinical data, blood count and chemistry were collected from medical records. To determine the in vitro effect of PTX3 on alternative pathway (AP) activation, sheep red blood cell-based hemolytic assay and AP activity ELISA were used. We found that PTX3 levels were elevated in the acute phase of STEC-HUS, aHUS and secondary TMA, whereas PTX3 elevation was exceptional is TTP. Conversely, a significantly higher median CRP was present in all patient groups compared to controls. PTX3, but not CRP was associated with signs of complement consumption in vivo, and PTX3 significantly decreased the AP hemolytic activity in vitro. Our results provide a detailed description of acute phase-TMA patients’ complement profile linked to changes in the systemic pentraxin levels that may support further molecular studies on the function of PTX3 in disease pathogenesis and add to the laboratory assessment of complement consumption in TMA.